2017
DOI: 10.1017/s1751731116001440
|View full text |Cite
|
Sign up to set email alerts
|

Current available strategies to mitigate greenhouse gas emissions in livestock systems: an animal welfare perspective

Abstract: Livestock production is a major contributor to greenhouse gas (GHG) emissions, so will play a significant role in the mitigation effort. Recent literature highlights different strategies to mitigate GHG emissions in the livestock sector. Animal welfare is a criterion of sustainability and any strategy designed to reduce the carbon footprint of livestock production should consider animal welfare amongst other sustainability metrics. We discuss and tabulate the likely relationships and trade-offs between the GHG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 50 publications
1
70
0
16
Order By: Relevance
“…Preventive health measures can play a role in increasing growth and fertility rates, which improve animal and herd performance [1]. Llonch et al [27] reported a reduction in rumen methanogenesis in response to an increase in production efficiency caused by improvements in the health status of the herd, which is a win-win strategy, because it increases environmental sustainability and animal welfare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preventive health measures can play a role in increasing growth and fertility rates, which improve animal and herd performance [1]. Llonch et al [27] reported a reduction in rumen methanogenesis in response to an increase in production efficiency caused by improvements in the health status of the herd, which is a win-win strategy, because it increases environmental sustainability and animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Many of those husbandry practices are associated with increases in productivity, which suggests that an economic benefit can be realized with a concurrent reduction in GHG emissions [27]. Strategies that both improve production efficiency and reduce GHG emissions are those most attractive to and most likely to be adopted by farmers [26].…”
Section: Discussionmentioning
confidence: 99%
“…The livestock sector exerts a large influence on global greenhouse gas (GHG) emissions [25]: Livestock-related emissions mainly concern methane (CH 4 ) and nitrous oxide (N 2 O) and, to a lower extent, carbon dioxide (CO 2 ). CH 4 emissions are a by-product of enteric fermentation and of manure management; N 2 O emissions come from manure management, and from manure applied to soil or left on pasture [29].…”
Section: A Quantification Of the Environmental Impactsmentioning
confidence: 99%
“…Livestock production contributes to greenhouse gas emissions [1]. Amongst a wide range of possible mitigation strategies to either reduce total emissions or reduce emissions intensity is achieving higher productivity, for example, through breeding or through intensive housing and concentrate feeding.…”
Section: Introductionmentioning
confidence: 99%